An Examination of the Provision of Supplemental Educational Services in Nine Rural Schools - Zoe A. Barley; Sandra Wegner (Journal of Research in Rural Education, 2010)
Under the No Child Left Behind Act schools that fail to make progress in having students reach proficiency are designated in "need of improvement." If this continues, schools that receive federal Title I funds are required to offer their low income students supplemental educational services (SES) such as tutoring outside of school time. Across the nation the percent of eligible students who actually participate in these services has been quite low, at 20% or less. A prior study found an even lower percent (11%) in seven states in the High Plains and found that for rural schools the program was even less successful. This study used interview date from nine rural public schools in order to identify underlying issues with eligible student participation. Implementing the SES program successfully has proven difficult for eight of the nine rural schools in this study with student participation 5% or less in seven of the nine schools. Four variables were examined:1) the extent to which school and district personnel valued SES programs; 2) the relationships established with service providers; 3) outreach to parents, and; 4) barriers to service delivery including transportation problems, lack of Internet access, lack of trust in outsiders, and logistical barriers associated with serving remote rural areas. We also sought to identify what solutions to the barriers were found. The authors recommend additional funding to states to assist high poverty low achieving rural schools in implementing the program.